Fiber Mode Scrambler for the Subaru Infrared Doppler Instrument (IRD). (16th April 2018) - Ishizuka, Masato; Kotani, Takayuki; Nishikawa, Jun; Kurokawa, Takashi; Mori, Takahiro; Kokubo, Tsukasa; Tamura, Motohide
Abstract: We report the results of fiber mode scrambler experiments for the Infra-Red Doppler instrument (IRD) on the Subaru 8.2-m telescope. IRD is a fiber-fed, high precision radial velocity (RV) instrument to search for exoplanets around nearby M dwarfs at near-infrared wavelengths. It is a high-resolution spectrograph with an Echelle grating. The expected RV measurement precision is ∼1 m s −1 with a state of the art laser frequency comb for the wavelength calibration. In IRD observations, one of the most significant instrumental noise is a change of intensity distribution of multi-mode fiber exit, which degrades RV measurement precision. To stabilize the intensity distribution of fiber exit an introduction of fiber mode scrambler is mandatory. Several kinds of mode scramblers have been suggested in previous research, though it is necessary to determine the most appropriate mode scrambler system for IRD. Thus, we conducted systematic measurements of performance for a variety of mode scramblers, both static and dynamic. We tested various length multi-mode fibers, an octagonal fiber, a double fiber scrambler, and two kinds of dynamic scramblers, and their combinations. We report the performances of these mode scramblers and propose candidate mode scrambler systems for IRD.